Simulation‐Assisted Localized DNA Logical Circuits for Cancer Biomarkers Detection and Imaging. Issue 49 (26th October 2022) - Kou, Qiaoni; Wang, Lei; Zhang, Linghao; Ma, Liang; Fu, Shengnan; Su, Xin
Abstract: DNA‐based nanodevices equipped with localized modules have been promising probes for biomarker detection. Such devices heavily rely on the intramolecular hybridization reaction. However, there is a lack of mechanistic insights into this reaction that limits the sensing speed and sensitivity. A coarse‐grained model is utilized to simulate the intramolecular hybridization of localized DNA circuits (LDCs) not only optimizing the performance, but also providing mechanistic insights into the hybridization reaction. The simulation guided‐LDCs enable the detection of multiple biomarkers with high sensitivity and rapid speed showing good consistency with the simulation. Fluorescence assays demonstrate that the simulation‐guided LDC shows an enhanced sensitivity up to 9.3 times higher than that of the same probes without localization. The detection limits of ATP, miRNA, and APE1 reach 0.14 mM, 0.68 pM, and 0.0074 U mL −1, respectively. The selected LDC is operated in live cells with good success in simultaneously detecting the biomarkers and discriminating between cancer cells and normal cells. LDC is successfully applied to detect the biomarkers in cancer tissues from patients, allowing the discrimination of cancer/adjacent/normal tissues. This work herein presents a design workflow for DNA nanodevices holding great potential for expanding the applications of DNA nanotechnology in diagnostics and therapeutics. Abstract : A DNA‐based nanodevice is developed by the guidance of coarse‐grained model simulation allowing for the detection and imaging of cancer biomarkers with high sensitivity and rapid response speed. The experimental results show good consistency with simulation prediction. This work offers significant guidance for the rational design of DNA‐based nanoprobes.